(untitled) (Economic studies journal, 2022)
The study aimed to measure and analyze the causal relationship between government revenues and expenditures in the public budget in Libya during the period from 1990 to 2020, the study used autoregressive vector methodology and Granger causality in the short term. The study also aimed to test the impulse response functions and Variance Decomposition to predict the impact of Random shocks on the study variables. The study concluded that there is a two-way causal relationship between government revenues and government expenditures in line with the hypothesis of "fiscal synchronization" in economic thought.